PEMBINGKAIAN ATLET PEREMPUAN PADA AJANG OLIMPIADE TOKYO 2020 DI MEDIA ONLINE OKEZONE.COM DAN KOMPAS.COM - Chrisintya Mauli Sitorus; Wiwid Noor Rakhmad; Nurul Hasfi (Interaksi Online, 2023)
Media reporting on female athletes still has some problems. Starting from stereotypes, sexism, objectification, commodification, and their voices that aren't represented proportionally. In Indonesia, the masculine culture embedded in sports and media often ignores the abilities and achievements of female athletes. This study used the critical constructivism paradigm to find out how female athletes are represented through the framing in the online media Okezone.com and Kompas.com during the 2020 Tokyo Olympics. This study used Zhongdang Pan and Gerald M Kosicki's framing analysis. This model divides framing into four elements; syntactic structure, script structure, thematic structure, and rhetorical structure. Ten news, each from online media Okezone.com and Kompas.com from 22 July - 23 August 2021 used as data for this study. Findings from this study indicate that news titles published by Okezone.com are the result of commodification based on the objectification of female athletes' physical appearances. This can be seen through the syntactic structure used in headlines and leads. The dominant script structure prioritizes "who" and "what" and didn't fulfill the news comprehensiveness as it should. The thematic structure can be seen by the choice of words and how the sentences used in the news tend to objectify women by reducing their appearance. The dominant rhetoric emphasizes diction that focused on physical appearance. Meanwhile, Kompas.com news headline shows gender sensitivity in reporting female athletes. This can be seen by how Kompas.com's syntax emphasizes female athletes' struggles and their career journeys. The syntactic structure of news presented by Kompas.com fulfills the 5W+1H element of news and emphasizes the "how" element. The thematic structure highlights female athletes' achievement as the main theme. The rhetorical structure of the selected photos or images shows the professionalism of female athletes. Findings from this study also show that the representation of female athletes through the media framing of Okezone.com is that female athlete are described as attractive-looking figures seen from their style of dress, glamor life, and their appearance on the field. Meanwhile, there are five representations of female athletes by Kompas.com; (1) Tough, (2) Achievers, (3) Having a high fighting spirit, (4) Responsible, (5) Able to penetrate gender boundaries in sports and (6) Sportive.